Analysis of gelotophobia's researches results of patiens with mental disordes - Oxana Shportun (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2015)
The article is devoted to research and identify of specific nosology of gelotophobia, gelotophilia and katagelastisism in patients with mental disorders. The analysis of a broad pattern and symptoms of emotional states of gelotophobia of healthy people and people with schizophrenia is conducted.
Keywords: gelotophobia; neurotic symptoms; mentald isorders; social phobia